PENGARUH PENERAPAN E-GOVERNMENT DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA JAKARTA TANAH ABANG TIGA TAHUN 2023 - Nurmala, Hilda; Irawan, Bambang (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Based on data from Jakarta Tanah Abang Tiga Primary Tax Service Office, the low level of taxpayer compliance although the number of registered taxpayers increases every year, the number of tax payers reporting tax returns is relatively low, There are significant fluctuations in the number of taxpayers reporting tax returns. In 2022, the realization (8,938) was higher than the number of taxpayers reporting tax returns (8,620), which resulted in a percentage above 100% (103.69%). This indicates a discrepancy in the data or there may be other influencing factors. This indicates that taxpayer compliance at Jakarta Tanah Abang Tiga Primary Tax Service Office is not yet optimal. This research used quantitative methods and the sampling method used simple random sampling method. The conclusion in this research is that the Implementation of E-Government has a positive and significant effect on Taxpayer Compliance at the Jakarta Tanah Abang Tiga Primary Tax Service Office. The magnitude of the effect of E-Government implementation on taxpayer compliance is 9.96%%. Service Quality has a positive and significant effect on Taxpayer Compliance at the Jakarta Tanah Abang Tiga Primary Tax Service Office. The magnitude of the effect of Tax Service Quality on Taxpayer Compliance is 21.28%. E- Government Implementation and Tax Service Quality simultaneously affect Taxpayer Compliance at the Jakarta Tanah Abang Tiga Primary Tax Service Office. The magnitude of the influence of E-Government Implementation and Tax Service Quality on Taxpayer Compliance is 30.9%.